Pelatihan Administrasi Pemerintahan Desa Haurkuning Kecamatan Nusaherang Menggunakan Microsoft Office - Fitra Nugraha; Aji Permana; Aah Sumiah (Journal of Innovation and Sustainable Empowerment, 2026)
Improving the quality of village government administration services in the digital era is a necessity in order to be able to answer the increasingly complex demands of society. This service aims to provide concrete solutions through village government administration training using Microsoft Office software in Haurkuning Village, Nusaherang District. This community service activity begins with a background analysis, where Haurkuning Village as the object of service faces challenges in implementing information technology, especially in using Microsoft Office. Problem identification is carried out to determine specific training needs for village administration staff. The research method used is qualitative research with a case study approach. Data was collected through interviews, observation and documentation studies. The results of data analysis become the basis for designing and implementing village government administration training programs with a focus on Microsoft Office applications. The main aim of this research is to increase the understanding and skills of village administration staff in using Microsoft Office, so that administrative processes can run more efficiently. The benefits of this research involve strengthening the capacity of administrative staff, improving the quality of services to the community, and providing a reference for other villages wishing to adopt similar training programs. The results of the training program evaluation showed a significant increase in understanding and skills in using Microsoft Office by village administration staff. It is hoped that this positive implication can create an administrative environment that is more efficient and responsive to community needs, in line with the increasingly important role of information technology in village government in the digital era.